Effects of Polarization Mode Dispersion (PMD) on Raman Gain and PMD Measurement using an Optical Fibre Raman Amplifier - Boiyo, Kiboi; Kuja, S.; Waswa, D.; Amolo, G.; Gamatham, R. R. G.; Kipnoo, E. K. Rotich; Gibbon, T. B.; Leitch, A. W.R. (IEEE, 2013)
We experimentally investigate the effects of increase of the differential group delay (DGD) on Raman gain and gain value. It was found that the increase of DGD values lead to the formation and the increase in the number of ripples at the expense of gain. A Raman amplifier with gain of 6.65 dB has been experimentally designed using a 24 km-SMF fibre spool with a gain fluctuation of ±0.2dB. Measurement of PMD using an optical fibre Raman amplifier has also been investigated and validated. This work recommends low values of DGD to reduce signal and gain distortion.
Keywords: Stimulated Raman Scattering; Optical Fibre Raman Amplifier; DGD; PMD